Legal and religious perspectives on assisted reproductive technology: artificial insemination, in-vitro fertilisation and surrogacy / Nur Amalina Muhamad Ngadi … [et al.] - Muhamad Ngadi, Nur Amalina; Ayop, Nurul Nur Shahirah; Hajali, Nur Farhana Natasya; Raj Mohamed, Khairun Neesha (Faculty of Law, 2014)
The principle objective of this paper is to demonstrate the capability of implementing a law on assistive reproductive technology in Malaysia. The goal of this paper is to demonstrate the need and the practicability of implementing such law on a group of citizen of different beliefs and religion. In order to achieve this goal, we have compared and discussed existing laws in several countries worldwide and the laws are compared and discussed to address this issue. There are various types of law discussed including region-wise and religion-wise which will demonstrate a thorough scope of the law applied in most society. Hopefully, with the availability of this dissertation, we would be able to directly or indirectly contribute in the continuous research on the practicability of implementing such law in Malaysia.